PERAN ULAMA DALAM MASYARAKAT ACEH DARI MASA KEMASA - Jon Paisal (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2021)
Ulama are the inheritors of the Prophets to spread Islamic teachings through da'wah activities, in the capacity of the ulama as Warasatul-anbiya (heir of the Prophet), an ulama should have a role to continue the baton of the prophetic mission in continuing the Prophet's message, at least he must play the role of tablig, tabyin, tahkim and uswah to mankind. This study aims to discover the role of ulama in Acehnese society from time to time. In this study, using the literature study method, the data comes from books, journals, and articles which can provide information on the role of ulama in Acehnese society from time immemorial. The results showed that the ulama had played a role in all aspects of community life in Aceh from time to time, including. The role of the ulama as a teacher in society, the ulama played a role in fighting the Dutch and the conflicts in Aceh, the ulama had a role in the post-Aceh conflict. The role of Ulama towards adat in society until now.